2004
DOI: 10.1079/ber2003278
|View full text |Cite
|
Sign up to set email alerts
|

Seedling and adult plant resistance to Sitobion avenae (Hemiptera: Aphididae) in Triticum monococcum (Poaceae), an ancestor of wheat

Abstract: Cereal aphids are important pests of wheat, Triticum aestivum L. and Triticum durum Desf. Crop resistance is a desirable method for managing cereal aphids in central North America, where the dominant crop, spring-sown wheat, has a low value per unit area. A diploid ancestor of wheat, Triticum monococcum L., is reported to be partially resistant to Sitobion avenae (Fabricius), the most damaging cereal aphid in the region. To identify potential sources of resistance, 42 accessions of T. monococcum and three cult… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
12
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(13 citation statements)
references
References 24 publications
1
12
0
Order By: Relevance
“…Migui & Lamb (2004) hypothesised that the resistance level of T. monococcum to S. avenae in seedlings could be because of the relative levels of hydroxamic acids (HAs) as reported in Leszczynski et al (1992). Elek et al (2012) observed reduced fecundity by R. padi on some T. monococcum lines.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Migui & Lamb (2004) hypothesised that the resistance level of T. monococcum to S. avenae in seedlings could be because of the relative levels of hydroxamic acids (HAs) as reported in Leszczynski et al (1992). Elek et al (2012) observed reduced fecundity by R. padi on some T. monococcum lines.…”
Section: Introductionmentioning
confidence: 99%
“…Triticum monococcum (L.) lines, in particular, have shown evidence of complete or partial resistance to pathogens and aphids (Spiller & Llewellyn, 1986; Migui & Lamb, 2004; Jing et al , 2007; Elek et al , 2012). Although seldom planted or harvested today, domesticated T. monococcum was an agriculturally important crop in the Neolithic through to the Bronze Age (Salamini et al , 2002).…”
Section: Introductionmentioning
confidence: 99%
“…We did not, however, see a difference in average performance of R. padi and S. avenae between the two collections, suggesting that during modern plant breeding, where improvements have focussed mainly on maximising yield, the plant effect on these aphid species has not been altered. In fact it could be inferred that a general loss of resistance traits happened before the rise of landraces, as resistance to aphid species has been reported in a number of diploid ancestors of wheat (Lamb & Migui, 2003; Migui & Lamb, 2004; Radchenko, 2011; Elek et al , 2013). …”
Section: Discussionmentioning
confidence: 99%
“…This is interesting and suggests that there is a pre‐alighting cue deterring the aphid settlement, which could have important implications for aphid management in wheat production and should be studied further. It also demonstrates differences in aphid preference and performance on older plants in the field compared with seedlings in the laboratory, highlighting the need for phenotyping for aphid resistance at different plant growth stages (Migui & Lamb, 2004). This would be greatly improved by incorporating new technologies which would make field assessments less labour intensive.…”
Section: Discussionmentioning
confidence: 99%
“…A few previous studies have assessed the development of aphid populations in field trials on wheat germplasm previously evaluated under controlled conditions, e.g. Randolph et al (2003) for Diuraphis noxia (Mordvilko) and Migui and Lamb (2004) for S. avenae.…”
Section: Introductionmentioning
confidence: 99%